PEMBUATAN NATA DARI AIR NIRA (Nata de Pinnata) SEBAGAI PRODUK SEHAT BERNILAI EKONOMI TINGGI - Pertiwi, Emi; Supriani, Dina; Bima Fahlevi, Muammar; Khaerunnisa, Iqlima; Asmawati, Ismi; Rizqi Alfian, Muhammad; Yuliana Pratiwi, Erika; Nisa, Hidayatun; Ilham, Rozal; Dilla Harpama, Nindya Farah; Zikro, Muhammad; Rachmayani, Ika (Universitas Mataram, 2025)
Keru Village is one of the villages in the Narmada District that has abundant wealth and potential resources. With a significant area of ​​agricultural land, this village is known as an agricultural area with high agricultural productivity. Fertile soil and a supportive climate allow the people of Keru Village to utilize the land as an agricultural sector. Keru Village is known for its aren tree plantations spread across various locations. The aren tree not only functions as a provider of sap for making palm sugar, but also makes an important contribution to biodiversity and environmental sustainability. In order to optimize the potential of aren processing in Keru Village, efforts are needed to provide training to the people of Keru Village in making nata de nira. By utilizing aren sap as a raw material for making nata, it is hoped that the people of Keru Village can master the technology of making nata de pinnata so that they can increase the economic value of their agricultural products and increase the variety of food products produced. Diversification of processed aren sap products into nata de pinnata will not only open up new market opportunities, but also contribute to increasing community income and the village economy. In addition, this effort is in line with the principle of sustainable development, namely the optimal use of natural resources without ignoring environmental aspects.